Pengaruh Rekrutmen dan Seleksi Karyawan terhadap Kinerja Karyawan pada CV. LPK Gintar Course - Putri Handayani; Nora Anisa Br. Sinulingga (Institute of Computer Science (IOCS), 2018)
This research was done in CV. LPK Gintar Course which was a company engaged in embroidery and embroidery learning services. The purpose of this study was to determine the effected of partial and simultaneous recruitment and selection toward employees performance. This type of research used correlational, the population were employees who worked in CV. LPK Gintar Course in 2018 as many as 35 people, sampling by means of saturated samples so that the total sample of 35 respondents. Data sources using primary data, data collection techniques using literature studies and surveys. Data analysis techniques using multiple linear regression, test classic assumptions and hypothesis testing. Based on the results of the study showed that partially and simultaneously recruitment and selection had positive and significant effected toward employees performance in the CV. LPK Gintar Course. The coefficient of determination showed that the value of R = 0.831, means that recruitment and selection have very strong relationship toward employee performance. R square coefficient value (R2) of 0.690 showed that employee performance could explained by recruitment and selection by 69% and the other amount of 31% could explained by other variables did not examined such as career planning, incentives, compensation, training, career planning, job promotions etc.